A study to evaluate the role of intradermal and intralesional measles, mumps, rubella (MMR) vaccine in treatment of common warts - Pragya Gupta; Geeta Ram Tegta; G K Verma; Abhishek Gupta; Mudita Gupta; Shikha Sharma (Wolters Kluwer Medknow Publications, 2020)
Background: Warts are common cutaneous viral infection with a wide range of therapeutic modalities. Various agents have been tried for immunotherapy in warts. Objectives: Determine the role of intralesional and intradermal measles, mumps, rubella (MMR) vaccine in the treatment of common warts; to compare the efficacy of intralesional versus intradermal MMR vaccine. Methods and Materials: Patients diagnosed with verruca vulgaris were divided into two groups. In study group A, the individuals were injected with an intralesional MMR vaccine of 0.3 mL in the representative wart (largest) once in 3 weeks till there is complete clearance or maximum of four injections whichever is earlier, while in study group B, the individuals were injected with an intradermal MMR vaccine of 0.3 mL over the unilateral deltoid muscle area at similar intervals. Results: There were 33 patients in each group. In group A, 10 (30.3%) patients showed complete, 9 (27.3%) marked, 6 (18.2%) moderate, 3 (9.1%) mild, and 5 (15.2%) no response. In group B, seven (21.2%) patients showed complete, one (3.0%) marked, one (3.0%) moderate, four (12.1%) mild, and 20 (60.6%) no response. There were minimal side effects in the form of pain, erythema, itching at the injection site in a few patients, only one patient had syncope. Conclusion: We conclude that the MMR vaccine is an effective and safe modality of treatment for verruca vulgaris without any serious adverse effects. Also, the intralesional route showed better results in comparison to the intradermal route when we consider the treatment of a representative wart.